The reckoning - Katsu, Alma (Arrow Books, 2013)
I turned to Luke and reached for him. Luke asked. He's free."For 200 years she's been hiding. He gave her immortality. She tried to destroy him. Now he is searching for her. They must not meet. Or there will be a reckoning.